The awakening course the secret to solving all problems - Vitale, Joe 1953- (Hoboken, NJ Wiley, 2011)
The author presents a program explaining the four stages of awakening. He offers a step-by-step approach for finding and achieving one's goals and desires, as well as a path to complete mind, body, and spiritual transformation
What to expect -- Stage one : victimhood -- Stage two : empowerment -- Stage 3 : Surrender -- Stage 4 : awakening -- The awakened millionaire -- The awakened relationship -- What do you want? -- Zero limit answers
Includes bibliographical references (p. 215-222) and index
1
Keywords: Life skills; Success; Transcendence (Philosophy); Wakefulness